1992
DOI: 10.1042/bj2820863
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of plasmin activity by oleic acid

Abstract: The amidolytic activity of plasmin with the chromogenic substrate H-D-valyl-L-leucyl-L-lysine p-nitroanilide (S-2251) is stimulated by oleic acid in a dose-dependent and saturable fashion. The activity of plasmin on S-2251 in the presence of oleic acid followed a sigmoidal kinetic pattern, with an almost 4-fold stimulation of activity at 60 microM-oleic acid. Half-maximal stimulation occurred at an oleic acid level of 19.5 microM. The amino acid analogue 6-aminohexanoic acid (AHA), which is known to bind to ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The phenomenon is similar to that induced by other ligands which bind to LBS in the plasmin, such as aspirin [36] and oleic acid [37].…”
Section: Discussionmentioning
confidence: 57%
“…The phenomenon is similar to that induced by other ligands which bind to LBS in the plasmin, such as aspirin [36] and oleic acid [37].…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that plasmin can act on the MFGM (e.g., via proteolysis of butyrophilin; Montagne, Girardet, & Humbert, 1999). It has also been reported that plasmin activity and the activation of plasminogen can be stimulated by oleic acid (Higazi, Finci-Yeheskel, Samara, Aziza, & Mayer, 1992) but it is not clear if this indicates a link between proteolysis and lipolysis in milk, as these observations were not studied in that medium. Furthermore, products of lipid oxidation may influence the activity of plasmin in milk, either by reacting directly with the enzyme molecule or by modification of the casein substrate (e.g., by forming Schiff's bases).…”
Section: Article In Pressmentioning
confidence: 94%
“…The presence of FN-II modules allows gelatinases A and B to bind and degrade insoluble elastin, a highly hydrophobic extracellular matrix macromolecule (16,39). Binding of long-chain fatty acids to kringles was found to modulate plasmin activity toward both synthetic substrate and fibrinogen (20,21). The involvement of the FN-II modules of gelatinase A in its inhibition by fatty acids was therefore investigated.…”
Section: Effect Of Elaidic Acid On the Degradation Of Human Skin Collmentioning
confidence: 99%
“…They bind to serine proteinases such as neutrophil elastase (18,19) and plasmin (20,21) and modulate their catalytic activities. Studies by Suzuki et al (22) show that oleic acid, 18-carbon fatty acid with one double carbon bond in the cis position, partially inhibits the formation of lung metastases from subcutaneous implantation of colon carcinoma cells in athymic mice.…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%